A systematic assessment of the occurrence of trace element hyperaccumulation in the flora of New Caledonia. (21st July 2020) - Gei, Vidiro; Isnard, Sandrine; Erskine, Peter D; Echevarria, Guillaume; Fogliani, Bruno; Jaffré, Tanguy; van der Ent, Antony
Abstract: New Caledonia is a global biodiversity hotspot known for its metal hyperaccumulator plants. X-ray fluorescence technology (XRF) has enabled non-destructive and quantitative determination of elemental concentrations in herbarium specimens from the ultramafic flora of the island. Specimens belonging to six major hyperaccumulator families (Cunoniaceae, Phyllanthaceae, Salicaceae, Sapotaceae, Oncothecaceae and Violaceae) and one to four specimens per species of the remaining ultramafic taxa in the herbarium were measured. XRF scanning included a total of c . 11 200 specimens from 35 orders, 96 families, 281 genera and 1484 species (1620 taxa) and covered 88.5% of the ultramafic flora. The study revealed the existence of 99 nickel hyperaccumulator taxa (65 known previously), 74 manganese hyperaccumulator taxa (11 known previously), eight cobalt hyperaccumulator taxa (two known previously) and four zinc hyperaccumulator taxa (none known previously). These results offer new insights into the phylogenetic diversity of hyperaccumulators in New Caledonia. The greatest diversity of nickel hyperaccumulators occur in a few major clades (Malphigiales and Oxalidales) and families (Phyllanthaceae, Salicaceae, Cunoniaceae). In contrast, manganese hyperaccumulation is phylogenetically scattered in the New Caledonian flora.